Anti-osteoporotic treatments in France: initiation, persistence and switches over 6 years of follow-up. Issue 3 (March 2017) - Belhassen, M.; Confavreux, C.; Cortet, B.; Lamezec, L.; Ginoux, M.; Van Ganse, E.
Abstract Summary Limited information is available on anti-osteoporotic treatment initiation patterns in France. In 2006–2013, the most frequently prescribed first-line treatment class for osteoporosis was represented by bisphosphonates (alendronic acid and risedronic acid), followed by strontium ranelate. Persistence with anti-osteoporotic treatment was low, with high proportions of treatment discontinuations and switches. Introduction This epidemiological, longitudinal study described first-line treatment initiation, persistence, switches to second-line treatment, and medical care consumption in osteoporotic patients in France during the 2007–2013 period. Methods Patients aged ≥50 years, who were recorded in a French claims database and did not die during the observation period, were included if they met ≥1 inclusion criteria for osteoporosis in 2007 (≥1 reimbursement for anti-osteoporotic treatment, hospitalisation for osteoporotic fracture (spine, hip, femur, forearm bones, humerus, wrist), or ≥1 reimbursement for long-term osteoporosis-associated status). We collected data on consumption of anti-osteoporotic treatment (alendronic acid, ibandronic acid, risedronic acid, zoledronic acid, raloxifene, strontium ranelate, teriparatide) and of osteoporosis-related medical care after the date of first reimbursement for anti-osteoporotic treatment. Results We obtained 2219 patients with a 6-year follow-up and 1387 who initiated an anti-osteoporotic treatment in 2007 and who can be selected for the treatment regimen analysis. The most frequently used first-line treatments were alendronic acid (32.7 %), risedronic acid (22.4 %), strontium ranelate (19.3 %), ibandronic acid (13.1 %) and raloxifene (12.2 %). Among patients who received these treatments, the highest persistence after 6 years was observed for raloxifene (37.3 %), alendronic acid (35.1 %) and risedronic acid (32.3 %). Treatment discontinuations were reported for 35.5 % (raloxifene) to 53.4 % (strontium ranelate) and treatment switches for 27.4 % (alendronic acid) to 56.6 % (ibandronic acid) of these patients. Conclusions This study showed that persistence with anti-osteoporotic treatment was relatively low in France, with high proportions of treatment discontinuations and switches, and that patients with osteoporosis were insufficiently monitored by bone specialists.